Howard's Long March The Strategic Depiction of China in Howard Government Policy, 1996-2006 - Campbell McDowall, Roy (Canberra Papers on Strategy and Defence, 2009)
Australia's strategic depiction of China has assumed increased importance as it attempts to harmonise economic interests (focusing on China) with security interests (primarily the United States). In this period of strategic transition, how Australia incorporates the rise of China into its existing security commitment under ANZUS has become a delicate issue. This investigation follows the intriguing evolution of the Howard Government's depictions of China, and reveals a complex and calculated strategy that successfully transformed a potentially volatile conflict of interests into a functional foreign policy.